Abdominal cocoon: Classic computed tomography images - Mohd Ilyas; Tameem Ahmad Bhat; Kifayat Hussain Ganaie; Tariq Gojwari (Wolters Kluwer Medknow Publications, 2018)
Abdominal cocoon is an uncommon cause of acute or subacute intestinal obstruction mostly secondary to tuberculosis. This report highlights the classic imaging features on computed tomography in a case of ileocecal tuberculosis with secondary abdominal cocoon.